AFLP assessment of genetic variability in cassava accessions (Manihot esculenta) resistant and susceptible to the cassava bacterial blight (CBB) - Sánchez, G.M.; Restrepo, S.; Duque E., Myriam Cristina; Fregene, Martin A.; Bonierbale, Merideth W.; Verdier, Valerie M. (Canadian Science Publishing, 1999)
Cassava bacterial blight (CBB) is caused by Xanthomonas axonopodis pv. manihotis (Xam). Resistance is found in Manihot esculenta and, in addition, has been introgressed from a wild relative, M. glaziovii. The resistance is thought to be polygenic and additively inherited. Ninety-three varieties of M. esculenta (Crantz) were assessed by AFLPs for genetic diversity and for resistance to CBB. AFLP analysis was performed using two primer combinations and a 79.2% level of polymorphism was found. The phenogram obtained showed between 74% and 96% genetic similarity among all cassava accessions analysed. The analysis permitted the unique identification of each individual. Two Xam strains were used for resistance screening. Variation in the reaction of cassava varieties to Xam strains was observed for all plant accessions. The correlation of resistance to both strains, had a coefficient of 0.53, suggesting the independence of resistance to each strain. Multiple correspondence analysis showed a random distribution of the resistance/susceptibility response with respect to overall genetic diversity as measured by AFLP analysis. A total heterozygosity index was calculated to determine the diversity within clusters as well as among them. Our results demonstrate that resistance to CBB is broadly distributed in cassava germplasm and that AFLP analysis is an effective and efficient means of providing quantitative estimates of genetic similarities among cassava accessions.Key words: amplified fragment length polymorphism, genetic base, resistance screening, Xanthomonas axonopodis pv. manihotis.